Tactical Masters Athletes: BMI Index Classifications - Marc Keefer; Joe Walsh; Kent Adams; Mike Climstein; Chad Harris; Mark DeBeliso (MDPI AG, 2022)
Understanding the nexus between aging, physical activity, and obesity has been a source of ongoing investigation. A considerable amount of research has focused on Masters athletes in this regard, suggesting a beneficial relationship between Masters sport participation and a healthy body mass index (BMI). Some consider Active Duty military personnel as tactical athletes. As such, it is of interest to determine if aging Active Duty military personnel (or Masters Tactical Athletes) might have a similar BMI as other Masters athletes (MA). As such, this investigation examined previously recorded data of Active Duty Enlisted United States Marines (n = 402, male, 46-50 years old). The BMI of the Marines was stratified into categories of: underweight, normal, overweight, and obese. The Marines obesity prevalence was compared to US adult males (40-59 years) as well as male North American MA who competed at the 2009 Sydney World Masters Games. The Marines obesity prevalence was significantly lower than US adult males (p < 0.001) and those MA that competed in softball (p < 0.001); however, it was similar to MA that competed in football, track/field, swimming, and volleyball (p > 0.05). The average Marine BMI = 26.7 kg/m2 was similar to MA who competed in football, swimming, and volley ball (p > 0.05); however, it was higher than MA who competed in track/field (p < 0.05) and lower than MA who played softball (p < 0.05). It should be noted that the average BMI for the Marines and all MA sport categories were classified as being overweight. Within the parameters of this investigation, Tactical MA (i.e., aging US Marines) enjoy a similar beneficial BMI as other North American MA.